Training Future Library Professionals to Use Neural Networks in Socio-Cultural Activities - E. Yu. Kozlenko (Библиосфера)
The effectiveness of the socio-cultural activities of libraries depends largely on the professionalism of the staff, their communication skills, creativity and skills in the use of digital technologies. The relevance of the article is determined by the increasing popularity of neural networks, their implementation in various spheres of human activity. The aim of the article is to examine the possibilities of the formation of competences on the use of neural networks in socio-cultural activities in the students of library and information studies, as well as to determine the readiness of students to perceive all aspects of the use of neural network algorithms. In the article, the analysis of publications and express survey was conducted. The latter was performed among the third and fourth year students of the Belarusian State University of Culture and Arts, who are studying on the speciality "Library and Information Activities". An attempt is made to diversify the potential of neural networks for training a competent specialist in the socio-cultural activity of libraries. The results of the study show the following. In training library and information workers on the use of neural networks in socio-cultural activities the key conditions are as follows: study and analysis of the experience of libraries in the use of neural networks in sociocultural activities; introduction into the educational programme of theoretical and practical blocks on the use of neural networks in the sociocultural activities of libraries; accounting and risk management of the use of neural networks. In implementing the above, more attention should be paid to responsible, emotional, creative manifestations of activity in educational and production processes.